(3GdQhV GdCQL GdTeje GdYGWQ GdfSje GdeZfj Yf GdTOh hGdeOGeIs - (3GdQhej Gdecj GdegJGQj, GdegJGQ, EHQGgje Hf jhSa, J (B1071(3g`s
(3ChdgG (B:s
(3MeOG def LeY UaGJ GdMeO ef cd eG Ndb aj gPg GdChQGb deY JaQbJ aj GdeShOGJ eeG Qb hQGb bGd HYVge GdcJGH fYe GdCfjS aj MGdI GdhMOI hfYe GdLdjS aj MGdI GdbYOI hfYe GdeYQaI HHdGO GdZQHI hfYe GdfUM aj MGdI GdUMHI s
(3BNQgG (B:s
(3UaI LhGQT CaQGM EPG cGf HYO GdYUQ aGYdb Ydi OejI GdbUQ hCMVQ CSHGH GdaQM HGdTaY hGdhKQ hGOY ddNdjaI GdegOj hGHf CNjg GdMSGe HGdXaQ hGdfUQ aEPG hLHJ GdTeS HLfhHgG Ef QeJeG EMSGfg ahGUdG SLYceG aj eOMg ahGUdG Jes
(3JHUQI GdeDda (B:s
(3GdegJGQ LGAJ cdbH aj GdCYdGe haj fSNI fSje GdUHG GdeNWhWI (B, (3hcfSHI LGAJ aj eYLe GdeDdajf hgOjI GdYGQajfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\82s
(3gOjI GdYGQajf (B1\33s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs